Potential areas for establishing silvopastoral systems with Pinus lawsonii and two forages in Michoacán, Mexico - Sáenz-Ceja, Jesús Eduardo; Sáenz-Reyes, J. Trinidad; Muñoz-Flores, Hipólito Jesús; Rueda-Sánchez, Agustín; Castillo-Reyes, Francisco; Castillo-Quiroz, David (Ecosistemas y Recursos Agropecuarios, 2022)
Silvopastoral systems represent an alternative to the productionof forage for cattle grazing and firewood, the reduction of soil degradation, and the diversification of agriculture production. This study aimed to identify the potential areas for establishing silvopastoral systems consisting of Pinus lawsonii and two forage gramineous Eragrostis curvula and Chloris gayana, in the state of Michoacán, Mexico, including areas with degraded soils. First, the potential species distribution of the three species was modeled according to their elevation, mean annual precipitation, mean annual temperature, and soil type requirements. Then the polygons of each species were intersected to obtain the potential areas. Finally, such areas were overlapped with the shape of degraded soils. As a result, thepotential areas for silvopastoral systems with P. lawsonii and E. curvula were found in the Michoacan portion of the Neo-volcanic Axis on a surface of 190 918 ha in 61 municipalities. The suitable areas with P. lawsonii and C. gayana were found in theNeo-volcanic Axis and the Sierra Madre del Sur on a surface of 329 546 ha within 81 municipalities. Furthermore, 60.8% of the suitable area of P. lawsonii with E.curvula and 55.4% of P. lawsonii with C. gayana were found on degraded soils. The results show high potential for establishing silvopastoral systems with these species in Michoacán, which can recover degraded soils and provide forage for cattle and firewood for rural inhabitants.
Keywords: climatic envelope, erosion, geographic information systems, livestock, soil conservation